PENINGKATAN KEBERDAYAAN PELAKU UMK DI BALIKPAPAN DALAM BRANDING PRODUK HALAL GUNA MENDAPATKAN UNIQUE SELLING PROPORTITION - Rahem, Abdul; Prayoga, Adistiar; Soleh, Mochammad; Ekowati, Juni; Naufal, Adam Mochammad; Abdul Jabbar, Davano Al Raffi; Yaqin, Ainul (Jurnal Bakti untuk Negeri, 2025)
The empowerment of micro and small-sized enterprises (MSEs’) is essential to promoting an inclusive and sustainable economy. One approach is to develop an unique selling proposition for MSEs' products. The aim of the community services, (1) providing counselling related to the Halal Product Assurance System (SJPH) for MSEs; (2) providing counselling on the use of digital technology; and (3) providing consultation and facilitation related to halal certification, business legality, and businesses digitalization. The trend of halal certification registration in Balikpapan from 2019-2024 showed good growth, although it was not as important as the number of food and beverages MSEs in Balikpapan City. In this sense, the Universitas Airlangga team chose MSE actors from six sub-districts in Balikpapan City as the focus of this activities. The evaluation approach was carried out using outputs. In addition to documenting internal and external community services, the empowerment of business actors was measured. The Wilcoxon Signed Rank Test was used to determine the results. It is reasonable to assume that the counselling was effective. This activity is designed to empower MSEs’ and serve as a model for speeding halal certification while also establishing an inclusive and sustainable community-based economy (SDGs 8, 11, and 17).